2016
DOI: 10.1002/2015pa002870
|View full text |Cite
|
Sign up to set email alerts
|

South Pacific hydrologic and cyclone variability during the last 3000 years

Abstract: Major excursions in the position of the South Pacific Convergence Zone (SPCZ) and/or changes in its intensity are thought to drive tropical cyclone (TC) and precipitation variability across much of the central South Pacific. A lack of conventional sites typically used for multimillennial proxy reconstructions has limited efforts to extend observational rainfall/TC data sets and our ability to fully assess the risks posed to central Pacific islands by future changes in fresh water availability or the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In the Atiu sediment record (Fig. 3D) and also in the Society Islands (27) (Fig. 3C), this is evidenced by concomitant precipitation increases.…”
Section: Discussionmentioning
confidence: 82%
“…In the Atiu sediment record (Fig. 3D) and also in the Society Islands (27) (Fig. 3C), this is evidenced by concomitant precipitation increases.…”
Section: Discussionmentioning
confidence: 82%
“…The Mobile Founding Migrant models (5) that proposed a rapid movement into Remote Oceania also seems reasonable given the timing of dispersal and supporting genetic data (29), though it seems clear that the late expansion into East Polynesia was also the result of factors such as land distribution, technological advances in seafaring, and climate (12). There are indications that post-AD 1000, more favorable winds (22) and changes to long-term mean precipitation, with drier conditions in the west in the increase rainfall over East Polynesia (30) could have promoted eastward colonization. It has also been suggested that the punctuated temporal pattern of Pacific colonization could be associated to millennial variability of ENSO frequency and intensity and the changes to ease of eastward movement these generate (24).…”
Section: Discussionmentioning
confidence: 90%
“…However, the lack of inter-model agreement in the equatorial region for GPI and its individual components suggests that the anomalies there may not be a robust response to consistent forcing. South China Sea (Yu et al, 2009), Jaluit Atoll (this study), Tahaa, French Polynesia (Toomey et al, 2013(Toomey et al, , 2016b, and cave KNI-51, northwestern Australia (Denniston et al, 2015(Denniston et al, , 2016.…”
Section: Detection In a Climate Model Ensemblementioning
confidence: 82%
“…Recently, records of TC landfall have been constructed with high temporal resolution from speleothem proxies of cave flooding (Denniston et al, 2015) and proxies of sediment transport over coastal barriers, over fringing reefs, or into coastal karst basins Toomey et al, 2016b;Donnelly et al, 2015;van Hengstum et al, 2016van Hengstum et al, , 2014Lane et al, 2011;Gischler et al, 2008;Donnelly et al, 2001). These reconstructions extend the observational record by several millennia and reveal large centennial variability in TC activity.…”
Section: Expanding the Observational Recordmentioning
confidence: 99%
See 1 more Smart Citation